From Research to Numbers: Role of Universities in Social Innovation - Cunha, Jorge; Ferreira, Carla; Araújo, Madalena; Benneworth, Paul (Innovations in Industrial Engineering, 2022)
Commonly, social innovation is defined as new ideas proposals to the needs of humans. However, there is a lack of a well-definition comprehensive leading the fragmentation of field research. On the other hand, the contribution of universities for social innovation development is still less investigated. In this sense, this study intends to explore interrelations between universities and social innovation in relation to different lines of investigation employed. For this, a content analysis was applied to results obtained by Cunha et al. [1]. Five categories of analysis were defined. Findings revealed that there are a number of studies that applied qualitative research to investigate practical examples of social innovation inside of universities and few empirical studies. A link among keywords social innovation, higher education, and social entrepreneurship was found. Furthermore, the analysis showed that there is not a leader country but a distribution across several countries, where Spain and United Kingdom stand out. Thus, this result suggests that it would be helpful to develop an instrument to measure academics’ engagement with social innovation research and practice. In addition, this research contributes to current knowledge regarding the role of universities in social innovation model, providing new theoretical and practical insights of investigation.
N'AVONS PAS ACCÈS
Keywords: Europe; Rôle des universités